Reading Galvanometers: Reflecting on the Infrastructure and Instrumental Practice of Electrical Metrology at the University of Toronto - Weidenhammer, Erich; Fisher, Victoria; Yeang, Chen-Pang; Spurr, Ava; Finnigan, Patrick (Scientia Canadensis, 2024)
The methodology of experimental reenactment has typically been used by historians to better understand landmark experiments. In this paper, we apply this approach to the galvanometer, an instrument so fundamental to the study of electricity that we may consider it infrastructure underlying the teaching of physics and engineering through the 19th century and well into the 20th centuries. We study a selection of galvanometers from the University of Toronto Scientific Instruments Collection, using them to explore their institutional context. Finally, we operate a representative galvanometer to explore several of the teaching experiments undertaken by engineering and physics students of the late 19th and early 20th centuries.